Psychological Impact of Unwanted Pregnancy on Adolescents: A Literature Review - Ermiati M.Kep., Sp. Mat; Eko Nugraha; Nindi Pratiwi; Artanti Lathifah; Devi Nurrahmawati; Tri Karizma; Eka Turjanah (Journal of Nursing Care, 2021)
The unwanted pregnancy in adolescents is increasing every year. The impact of unwanted pregnancy towards the adolescents can form as physical and psychological. The psychological impact which is not resolved can result in depression and even suicide. The purpose of this literature review is to determine the psychological impact on adolescents who experience the unwanted pregnancy.This literature review used narrative review related to the psychological impact of adverse events on adolescents. The databases used for this study are Google Scholar, Science Direct, Proquest, Pubmed, Researchgate, and Garuda Portal. The keywords used in Indonesian are, dampak psikologis” dan “kehamilan tidak diinginkan” dan “remaja”. The English keywords are “impact” and “unwanted pregnancy” OR “unintended pregnancy”, “teenager” OR “adolescent”. 32 articles were obtained according to the inclusion criteria were open access, full texts with publication years between 2010-2020 and 9 articles were selected for further review. The results showed the psychological impact of the unwanted pregnancy on adolescents are shame, fear, disappointment, anxiety, crying, guilt, irritability, being introverted, frustrated, angry, aggressive, panic, regret, stress and depression. Suggestion: The results of this literature review are expected to be a reference in further and in-depth research regarding the impact of unwanted pregnancy on adolescents so that the number of unwanted pregnancies in adolescents will no longer increase if they know the impact of unwanted pregnancies.